Strategi Pengembangan Sumber Daya Manusia Sektor Pariwisata Melalui Partisipasi Masyarakat - Jusdiana Ahmad, Andi; Hakim, Lukman; Mustari, Nuryanti; Fatmawati, Fatmawati (Jayapangus Press, 2024)
This research purposes to develop a strategy for human resource development in the tourism sector through community participation. This research applied a qualitative approach with a purposive sampling method to select informants, including officials from the Tourism, Youth and Sports Office, the Human Resources Staffing and Development Agency, and community members, who have an important role in advancing tourism in the region. Data collection techniques included observation, interviews, and documentation, while analysis used triangulation of sources, methods, and time, supported by NVivo 12 Plus software. The results showed that tourism in Bulukumba plays an important role in improving the local and regional economy while facilitating knowledge exchange between tourists and local communities. However, sustainability issues underline the importance of improving human resources, especially in managing the tourism space. The government's strategy in this regard emphasizes inclusivity and active community participation. The involvement of various stakeholders, including community groups such as Pokdarwis (Kelompok Sadar Wisata), marks a collaborative effort to sustain and improve tourism in Bulukumba Regency.